PENGARUH PENERAPAN MODEL TGT TERHADAP TANGGUNG JAWAB BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA KELAS IV - Andre Rahmadin; Bistari Bistari; Tahmid Sabri (Universitas Tanjungpura, 2020)
AbstractThis research aims to analyze the influence of Implementating Teams Games Tournament Model of Student Learning Responsibilities in Learning Mathematics Class IV Public Elementary School Number 16 Pontianak Timur. Experimental method is in the form of quasy experimental research with nonequivalent control group design. Population is this research consists of 68 students. Sampling technique used is simple random sampling obtained from class IVA samples as the experimental class dan class IVB as the control class. Data collection used is indirect communication technique, with data collection tools in the form of learning responsibilities questionnaire and observation page of learning responsibilities. Based of research analysis and learning responsibilities questionnaire, it is obtained that which means Ha is accepted. Based on the calculation of Effect Size, observation pages responsibilities questionnaire has obtained 2,35 which is categorized as high criteria. It can be concluded that there is an influence Implementating Teams Games Tournament Model on Student Learning Responsibilities in Learning Mathematics Class IV Public Elementary School Number 16 Pontianak Timur. Keywords: Influence, Learning Responsibilities, Teams Games Tournament